Analysis of the Influence of Different Scanning Conditions of Medical Linear Accelerator CBCT on Image Quality - Li LIU; Chengwei YE; Jianjun YUAN; Yingui LUO; Zhiyao LUO; Wei ZENG; Ling LI; Huan LIU; Yan LIU (Zhongguo yiliao qixie zazhi)
ObjectiveTo investigate the influence of different scanning conditions on the image quality of medical electron accelerator cone-beam computed tomography (CBCT) and provide a reference for the selection of scanning conditions for different body parts. Methods Set different scanning conditions, the Catphan 503 phantom was scanned using CBCT parameters to analyze the influence of spatial resolution, noise, uniformity, spatial geometric accuracy, and low-contrast resolution on the image quality of CBCT. Results For the head, chest, and abdomen, with the increase in scanning parameter values, the noise value decreased by 47.4%, 26.1%, and 51.3% respectively, and the uniformity values decreased by 30.2%, 26.6%, and 47.9% respectively. The low-contrast resolution values decreased by 50.6%, 34.2%, and 12.0%. The influence of different scanning conditions on spatial geometric accuracy and spatial resolution is not significant. ConclusionDifferent scanning parameters have a certain influence on the image quality of medical electron accelerator CBCT. Lower scanning parameters can be selected based on individual patients to reduce the additional radiation dose, providing a reference for the safe application of CBCT image guidance in radiotherapy.